2020
DOI: 10.20944/preprints202008.0522.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Social Factors on Job Crafting: A Meta-analysis and Review

Abstract: Despite the considerable focus on job characteristics and individual differences in job crafting research, the influence of social factors on job crafting has not been well-acknowledged. This meta-analysis estimates the associations between social factors and job crafting, and how social factors contribute to employee outcomes through their job crafting. Based on a sample of 51 empirical studies that included 54 independent effect sizes (N = 17,863), we found that social factors of positive leadership styles … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 93 publications
(202 reference statements)
1
7
0
Order By: Relevance
“…The result for the same link was also found by previous studies (Slemp & Vella-Brodrick, 2014;Toyama et al, 2021). Through JC, employees can effectively deal with threats and stress, and thus resulting in a higher level of positive attitudes and job related well-being (Wang et al, 2020).…”
Section: -Discussion and Conclusionsupporting
confidence: 85%
See 3 more Smart Citations
“…The result for the same link was also found by previous studies (Slemp & Vella-Brodrick, 2014;Toyama et al, 2021). Through JC, employees can effectively deal with threats and stress, and thus resulting in a higher level of positive attitudes and job related well-being (Wang et al, 2020).…”
Section: -Discussion and Conclusionsupporting
confidence: 85%
“…Similarly, Rudolph et al ( 2017) proved that JC is positively correlated with job satisfaction and work engagement, while JC is negatively correlated with job strain. Previous empirical researches have revealed that JC is positively linked to EW (Slemp & Vella-Brodrick, 2014;Wang et al, 2020;Toyama et al, 2021). Therefore, based on the previous arguments, the following hypothesis was formulated: H5: Job crafting is positively related to employee wellbeing.…”
Section: Job Crafting and Employee Wellbeingmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing autonomy and job support, derived from empowering leadership and job crafting behaviors, motivate employees to set boundaries and perceptions of their work roles. Consequently, the level of task performance and positive influence in the workplace will be higher [11]. Job crafting improves employee job performance [12].…”
Section: Introductionmentioning
confidence: 99%